Back to the Future? The Emergence of a Geneticized Conceptualization of Race in Sociology. Issue 1 (September 2015) - Frank, Reanne
Discoveries in human molecular genetics have reanimated unresolved debates over the nature of human difference. In this context, the idea that race has a discrete and measurable genetic basis is currently enjoying a resurgence. The return of a biologized construction of race is somewhat surprising because one of the primary pronouncements to come out of the Human Genome Project was one of human genetic similarity (i.e., humans are over 99.9 percent similar at the molecular level). Perhaps even more surprising is that genetically based notions of race have not been restricted to the biomedical sciences but have recently emerged within the social sciences, specifically sociology, to explicitly challenge a socially constructed understanding of race. Drawing on existing critiques, this article describes problems in recent sociological scholarship and the potential role of social scientists in future work occurring at the intersection of race and genetics. I argue that recent scholarly work meant to challenge the notion of race as a social construction actually makes a powerful case for its continued utility.